The Love of God : Divine Gift, Human Gratitude, and Mutual Faithfulness in Judaism - Levenson, Jon Douglas (Book collections on Project MUSE., 2016)
The love of God is perhaps the most essential element in Judaism--but also one of the most confounding. In biblical and rabbinic literature, the obligation to love God appears as a formal commandment. Yet most people today think of love as a feeling. How can an emotion be commanded? How could one ever fulfill such a requirement? The Love of God places these scholarly and existential questions in a new light. Jon Levenson traces the origins of the concept to the ancient institution of covenant, showing how covenantal love is a matter neither of sentiment nor of dry legalism. The love of God is instead a deeply personal two-way relationship that finds expression in God's mysterious love for the people of Israel, who in turn observe God's laws out of profound gratitude for his acts of deliverance. Levenson explores how this bond has survived episodes in which God's love appears to be painfully absent--as in the brutal persecutions of Talmudic times--and describes the intensely erotic portrayals of the relationship by biblical prophets and rabbinic interpreters of the Song of Songs. He examines the love of God as a spiritual discipline in the Middle Ages as well as efforts by two influential modern Jewish thinkers--Martin Buber and Franz Rosenzweig--to recover this vital but endangered aspect of their tradition. A breathtaking work of scholarship and spirituality alike that is certain to provoke debate, The Love of God develops fascinating insights into the foundations of religious life in the classical Jewish tradition.